The Role and Contribution of Indonesian Citizens in Efforts to Defend the Country in the Contemporary Era - Putri Fadilah Sari; Siti Fadillah Husna; Ilham Harahap; Okniel Nainggolan (Jurnal Pengetahuan Sosial dan Sejarah, 2025)
This article discusses the role and contribution of Indonesian citizens in national defense efforts in the contemporary era. This study uses a qualitative approach with a literature study method. The results of the study show that defending the country is a constitutional obligation of every Indonesian citizen which is not only limited to the military aspect, but also includes contributions in the social, economic, and cultural fields. However, in the contemporary era, Indonesia is faced with several challenges such as radicalism, terrorism, corruption, as well as the impact of the development of society 5.0 and technological advancements. To counteract radicalism and terrorism, efforts that can be made are to implement the values of Pancasila in the life of the nation and state. In addition, the role of the media is also important in spreading messages of peace and stopping the spread of radical ideas. Meanwhile, to deal with the problem of corruption, supervision and accountability are needed in the government system. Overall, this article emphasizes the importance of the active participation of all citizens in efforts to defend the country to maintain the integrity and safety of the Republic of Indonesia.